Longitudinal bidirectional associations of physical activity and depressive symptoms: The CARDIA study - Dong Zhang; Kelley Pettee Gabriel; Stephen Sidney; Barbara Sternfeld; David Jacobs Jr; Kara M. Whitaker (Preventive Medicine Reports, 2021)
Depression affects many aspects of health and may be attenuated through increases in physical activity. While bidirectional associations between physical activity (PA) and depressive symptoms have been examined, few studies have examined these associations using both self-reported and accelerometer-estimated measures. Using data from Years 20 (2005–06, age 38–50) and 30 of the Coronary Artery Risk Development in Young Adults (CARDIA) study (N = 2,871), the bidirectional associations between moderate to vigorous intensity physical activity (MVPA) and depressive symptoms were examined using a cross-lagged panel model. Differences in the observed associations by physical activity assessment method were also examined. An inverse bidirectional association between self-reported MVPA and depressive symptoms was found. In subsequent analyses stratified by intensity category, higher levels of vigorous intensity physical activity at baseline, but not moderate intensity physical activity were associated with lower levels of depressive symptoms at the 10-year follow-up (ϕ = −0.04, p < 0.01; ϕ = −0.03, p = 0.15, respectively). A 10-year increase in self-reported MVPA was associated with a 10-year decrease in depressive symptoms. No associations were observed between accelerometer MVPA estimates and depressive symptoms. These findings may support the notion that each assessment method captures related, but also unique, aspects of physical activity behavior. When possible, future studies should explore measures of association by each physical activity assessment method to gain a better understanding of the complex relationship between physical activity and health.